WNT4-like protein is a cortical granule component in mouse oocytes and functions in regulating preimplantation embryogenesis. (2nd January 2016) - Liu, Min; Yang, Huei-Ting
Abstract: Mammalian cortical granules (CG) are membrane-bound organelles located in the cortex of the unfertilized oocytes. Upon fertilization, CG undergo exocytosis to function in blocking polyspermy. While cortical granules are important in fertilization, their exact biochemical composition and reproductive function have not been fully defined. In the present study, a 66 kDa wingless-type MMTV integration site family, member 4 (WNT4)-like protein, with mouse CG origin was identified. Oocytes that were double labeled with lectin Lens culinaris agglutinin (LCA) and WNT4 antibody showed colocalization of the WNT4 molecules and cortical granules. The disappearance of WNT4 molecules in the artificially activated oocytes that were devoid of cortical granules confirmed their granule origin. Following fertilization, WNT4 remained associated with zygotes and blastomeres of 2-cell and 8-cell embryos; however the amount of protein present was reduced more than 2-fold as embryos developed. Prior to implantation, WNT4 appeared to be detectable only in the trophoblast cells. Our functional study revealed that WNT4 molecules were involved in regulating zygotic cleavage and early embryogenesis. To our knowledge, this is the first study demonstrating mammalian cortical granules contain signaling molecules that are involved in the regulation of the first phase of embryonic development.